Social media at the workplace: The relationship between techno eustress and employee performance at Universiti Malaysia Pahang / Nurul Aini Azhar - Azhar, Nurul Aini (Faculty of Business and Management, 2020)
Social Media at the Workplace: The Relationship Between Techno Eustress and Employee Performance at Universiti Malaysia Pahang (UMP). The purpose of this study was to investigate relationship between techno eustress and employee performance. The final report comprises of five chapters, where the first chapter introduction of the study. In chapter two cover literature review of the study and chapter three covers research methodology. Thus, in chapter four covers the finding and discussion and chapter five covers conclusion, recommendation and suggestion for future research. There are three research objective and research question and followed with two research hypothesis for this study. A total of 97 set of questionnaire were distributed to the employees at UMP by using simple random sampling. The questionnaire was constructed in both Malay and English. The questionnaire consists of three sections based on the variables of the study. Furthermore, the data gathered from the questionnaire was analyzed by using the Statistical Packages for Social Science (SPSS) Version 22.0. Then the data will be presented in form of frequency, percentage, and mean to show the relationship between techno eustress and employee performance. Researcher also recommend and suggests employer to encourage to use social media at the workplace and organization must consider social media as platforms to communicate with employees either inside or outside the organization